Relationship between surface properties and in vitro drug release from a compressed matrix containing an amphiphilic polymer materia. (2016)
The performance of compressed tablet drug delivery systems made using polymeric materials depend on multiple factors, such as surface properties like contact angle, surface free energy and water absorption rate, besides the release mechanisms driven by the kind of polymer used. Hence, it should be possible to establish a relationship between the surface properties and the drug release kinetics. Compressed tablets with different proportions of poly(maleic acid-alt-octadecene) potassium salt (0%, 10%, 20%, 30% and 40%) were prepared. Blends of a model drug (ampicillin trihydrate) and the polymer material were analyzed by DSC.